Membership categorization, humor, and moral order in sitcom interactions. (April 2022) - Okazawa, Ryo
Highlights: Production techniques and actors' work make moral order visible to remote audiences. Membership categorization is employed to invoke humor through moral order in sitcoms. Camerawork and actors' expressions make misunderstandings among characters visible. Characters show orientations to the moral culpability of misunderstanding. Abstract: By applying membership categorization analysis (MCA) to fictional discourse, this study investigates how various production techniques and actors' work are employed to make moral order visible to remote audiences in a humorous frame. Specifically, I focus on sitcom interactions in which misunderstandings regarding membership categorization practices are produced and managed among fictional characters. The analysis demonstrates that scriptwriters design characters' utterances ambiguously in terms of whether these utterances constitute membership categorization. By doing so, scriptwriters arrange fictional interactions involving characters' misunderstandings and moral conflicts. The camerawork, actors' gestures, and facial expressions also contribute to making visible the moral order and misunderstanding among fictional characters to remote audiences. The findings suggest that these production techniques are employed to produce humorous incongruities between a fictional character's accusation of others' morally problematic categorization practices and the character's own morally culpable categorization practices. This study extends MCA research by examining the invocation of humor through moral order in fictional discourse and shows that MCA approaches can contribute to humor research on scripted interactions.